Ready for college Doing laundry, writing papers, keeping your faith, passing exams, avoiding alcohol, making time, going on dates, eating healthhy, staying safe - Pennock, Michael Francis
The first year of college is among the most daunting a person will ever face. This freshman year begs for maximum up-front preparedness. Ready for College provides ways to plan and maintain finances, which supplies to bring and which to leave at home, how to avoid the pitfalls of dorm living, and much more. New students are also reminded to continue developing an ongoing relationship with Jesus.